2016
DOI: 10.1111/ijfs.13034
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of canola proteins extracted by electroactivated solutions in gluten‐free biscuit formulation of rice–buckwheat flour blend: assessment of quality characteristics and textural properties of the product

Abstract: Canola proteins extracted by electroactivated solutions were incorporated to gluten-free biscuits made from blend of rice and buckwheat flours. Physical and textural properties were significantly influenced by these proteins. Isolates and concentrates did not behave in a similar way. A significant increase in diameter was noted for all of the supplemented samples. An increase in thickness was observed for the samples added with protein concentrate, whereas the spread ratio decreased for all the samples compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
(92 reference statements)
1
7
0
1
Order By: Relevance
“…the spread ratio significantly. Other authors also observed a lower expansion in enriched cookies with the addition of sunflower (Claughton & Pearce, 1989), canola (Gerzhova et al, 2016), rice bran (Yadav et al, 2011) or gluten-soy (Singh & Mohamed, 2007) proteins, in agreement with the presented results for GP. Although these authors used different proteins, Souza et al (1994) stated that the total protein content is more important for sugar-snap cookie quality than is the composition of that protein.…”
Section: Cookie Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…the spread ratio significantly. Other authors also observed a lower expansion in enriched cookies with the addition of sunflower (Claughton & Pearce, 1989), canola (Gerzhova et al, 2016), rice bran (Yadav et al, 2011) or gluten-soy (Singh & Mohamed, 2007) proteins, in agreement with the presented results for GP. Although these authors used different proteins, Souza et al (1994) stated that the total protein content is more important for sugar-snap cookie quality than is the composition of that protein.…”
Section: Cookie Characteristicssupporting
confidence: 91%
“…In general, the addition of GP increased cookie height and decreased cookie diameter, reducing the spread ratio significantly. Other authors also observed a lower expansion in enriched cookies with the addition of sunflower (Claughton & Pearce, ), canola (Gerzhova et al ., ), rice bran (Yadav et al ., ) or gluten–soy (Singh & Mohamed, ) proteins, in agreement with the presented results for GP. Although these authors used different proteins, Souza et al .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, studies of protein enriched gluten-free cookies are limited. Of the few that exist, they have only included up to 20% of pea protein (Mancebo et al 2016), 10% of whey-soy protein blend or 9% of canola protein isolate (Gerzhova et al 2016). None compare different types of protein sources in this kind of cookie.…”
Section: Introductionmentioning
confidence: 99%
“…They found that increasing the relative amounts of buckwheat decreased biscuit hardness and fracturability. Similarly, Gerzhova, Mondor [35] have demonstrated that adding canola protein to 80% rice and 20% buckwheat flour biscuits decreased the hardness and increased thickness of the biscuit. Sarabhai and Prabhasankar [36] have reported that adding soy and whey protein to a rice flour biscuit reduced its breaking strength (and, therefore, the hardness).…”
Section: Discussionmentioning
confidence: 85%